From Necessity to Opportunity : Lessons for Integrating Phone and In-Person Data Collection for Agricultural Statistics in a Post-Pandemic World - Zezza, Alberto; Mcgee, Kevin; Wollburg, Philip; Assefa, Thomas; Gourlay, Sydney (World Bank, Washington, DC, 2022)
The COVID-19 pandemic has disrupted survey and data systems globally and especially in low- and middle-income countries. Lockdowns necessitated remote data collection as demand for data on the impacts of the pandemic surged. Phone surveys started being implemented at a national scale in many places that previously had limited experience with them. As in-person data collection resumes, the experience gained provides the grounds to reflect on how phone surveys may be incorporated into survey and data systems in low- and middle-income countries. This includes agricultural and rural surveys supported by international survey programs such as the World Bank’s Living Standards Measurement Study—Integrated Surveys on Agriculture, the Food and Agriculture Organization’s AGRISurvey, or the 50x2030 Initiative. Reviewing evidence and experiences from before and during the pandemic, the paper analyzes and provides guidance on the scope of and considerations for using phone surveys for agricultural data collection. It addresses the domains of sampling and representativeness, post-survey adjustments, questionnaire design, respondent selection and behavior, interviewer effects, as well as cost considerations, all with an emphasis on the particularities of agricultural and rural surveys. Ultimately, the integration of phone interviews with in-person data collection offers a promising opportunity to leverage the benefits of phone surveys while addressing their limitations, including the depth of content constraints and potential coverage biases, which are especially challenging for agricultural and rural populations in low- and middle-income countries.